Vertical Foreign Direct Investment versus Outsourcing: A Welfare Comparison from the Perspective of a Host Country - Goswami, Arti Grover (2012)
In the offshoring literature, there is a huge disconnect between the alternative modes of organizing offshore production and their relative welfare impact on a host country. We bridge this gap by comparing the welfare of a host country from vertical foreign direct investment (VFDI) vis-a-vis international outsourcing. Our model finds that the ability to maximize welfare in the alternative modes of organizing offshore production is contingent on the absorptive capacity of the host country. If a host country's absorptive capacity is above a critical threshold, outsourcing is more welfare enhancing vis-a-vis VFDI; while even with an absorptive capacity lower than this critical threshold, outsourcing being welfare improving over VFDI cannot be ruled out.